2015
DOI: 10.1007/s13361-015-1289-5
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Ionization-Desorption Analysis Source (MIDAS) for Mass Spectrometry: Thin-Layer Chromatography

Abstract: Abstract. Molecular ionization-desorption analysis source (MIDAS), which is a desorption atmospheric pressure chemical ionization (DAPCI) type source, for mass spectrometry has been developed as a multi-functional platform for the direct sampling of surfaces. In this article, its utility for the analysis of thin-layer chromatography (TLC) plates is highlighted. Amino acids, which are difficult to visualize without staining reagents or charring, were detected and identified directly from a TLC plate. To demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…Thus, the isolated ions at m / z 130 were used for quantitation. In general, a 2 to 4 orders magnitude improvement in the LODs was obtained, which is better than any of the LODs reported to date on plasma-based ambient desorption ionization MS from TLC plates, as discussed in the previous sections. ,,,, In addition, the LODs in Table are also comparable to the performance reported for amino acids with MALDI-TOF-MS . It needs to be pointed out that in that study standard solutions were directly pipetted on the MALDI sample plate, not on TLC plates where the desorption is affected by the strong interaction between the analyte and the TLC matrix, and using internal standards for quantitation.…”
Section: Resultsmentioning
confidence: 49%
See 1 more Smart Citation
“…Thus, the isolated ions at m / z 130 were used for quantitation. In general, a 2 to 4 orders magnitude improvement in the LODs was obtained, which is better than any of the LODs reported to date on plasma-based ambient desorption ionization MS from TLC plates, as discussed in the previous sections. ,,,, In addition, the LODs in Table are also comparable to the performance reported for amino acids with MALDI-TOF-MS . It needs to be pointed out that in that study standard solutions were directly pipetted on the MALDI sample plate, not on TLC plates where the desorption is affected by the strong interaction between the analyte and the TLC matrix, and using internal standards for quantitation.…”
Section: Resultsmentioning
confidence: 49%
“…For example, a detection limit of 370 ng for acetaminophen was reported by APCI-MS, in which the desorption was accomplished by a heated metal probe at 350 °C placed near-by or just touching the NP-TLC plate surface, whereas, in the present study, the LOD of 1.2 pg/mm 2 (∼11 pg per sample spot) for acetaminophen was achieved by LD-LTP, which is more than 4 orders of magnitudes better (Table ). In addition, the molecular ionization-desorption analysis source (MIDAS), with discharge nitrogen gas heated up to 180 °C, implemented for direct sampling from silica gel TLC plates showed a linear calibration curve from 50 to 1000 ng of caffeine per spot, no LODs reported . Another recent published study by Garcia-Rojas et al reported LODs of caffeine in 20 ng/mm 2 on polyethylene-supported TLC plates by LTP-MS with laser desorption .…”
Section: Resultsmentioning
confidence: 99%
“…One approach to reduce ion suppression and matrix effects is to combine ADI sources with planar chromatography techniques such as thin-layer chromatography (TLC) or high-performance thin-layer chromatography (HPTLC). For example, the benefit of coupling TLC to DESI-MS [ 15 17 ], DART-MS [ 18 20 ], low-temperature plasma (LTP) [ 21 ], and molecular ionization-desorption analysis source (MIDAS) [ 22 , 23 ] has been demonstrated in several studies. Other plasma-based ADI sources such as the flowing atmospheric-pressure afterglow (FAPA) source were used in TLC-ADI-MS studies as well [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…A filter paper containing algal agent was placed in the solid culture medium, and the ability of algal growth inhibition was determined by measuring the diameter of the blank region of the algae cell death in the solid medium. After comparing the inhibition zone diameters obtained using different extracts, the extract with the optimal inhibition on algal growth was selected for subsequent thin layer chromatography (TLC) [30,31] and column chromatography experiments for separation and purification.…”
Section: Extraction and Separation Of Compounds Present In E Dulcis mentioning
confidence: 99%